Linearity correction of two-dimension image in tomography gamma-camera - A. M. Sokolov (Ядерна фізика та енергетика)
On the base of image of regular grid hole phantom, which is obtained in gamma-camera without correction, description of direct mapping is made. Correcting mapping is build by means of specialy developed two-dimension interpolation procedure for non-regular net of points and then is used in correction unit.